DOI: 10.1007/978-3-540-74833-5_1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Spatial Aggregation on the Characteristics of Origin-Destination Pair Traffic in Funet

Abstract: In this paper we analyze measurements from the Finnish University Network (Funet) and study the effect of spatial aggregation on the origin-destination flows. The traffic is divided into OD pairs based on IP addresses, using different prefix lengths to obtain data sets with various aggregation levels. We find that typically the diurnal pattern of the total traffic is followed more closely by the OD pairs as their volume increases, but there are many exceptions. Gaussian assumption holds well for all OD pairs w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 17 publications
(25 reference statements)
0
9
0
Order By: Relevance
“…The main conclusion is that stationarity can be reasonably assumed to hold within periods of 30-90 min. The empirical studies performed in [15,11,16] for Funet data essentially confirm the stationarity assumption in [7] (again, a time aggregation from 1 s to 300 s is used).…”
Section: Introductionmentioning
confidence: 59%
See 3 more Smart Citations
“…The main conclusion is that stationarity can be reasonably assumed to hold within periods of 30-90 min. The empirical studies performed in [15,11,16] for Funet data essentially confirm the stationarity assumption in [7] (again, a time aggregation from 1 s to 300 s is used).…”
Section: Introductionmentioning
confidence: 59%
“…To justify this statement, we first remark that the expectations l X i s and the variances r 2 X i s are related by a monotone relationship: the larger the mean l X i , the larger the variance r 2 X i . More precisely, a power law r 2 X i ¼ cl 1=q X i (with c a suitable constant) is usually considered, with q = 1 as in [6], or q = 2/ 3, as in [16]. As a consequence, denoting by Nð0; 1Þ a standard normal distribution, we have…”
Section: The Traffic Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…The assumption of Gaussianity of the S-D bits (packets) arrival process is justified by (space/time) aggregation obtained by superimposing independent traffic processes (independent sources) satisfying the usual conditions of the functional central limit theorem (see Norros and Pruthi, 1996;Taqqu et al, 1997). The assumption has been considered in Cao et al (2000), Norros and Kilpi (2002), Juva et al (2005), Susitaival et al (2006) and Juva et al (2007), and validated via QQ-plots and related correlation tests that compare the empirical distribution with a fitted Gaussian distribution. The data at hand is traffic observed on one link partioned into S-D traffic based on source and destination IP address (time aggregation from 1 second to 300 seconds), except in Cao et al (2000) where data is traffic observed on the links and S-D pairs of a one-router network with 5 minutes time aggregation, as provided by Simple Network Management Protocol (SNMP).…”
Section: Discussion and Justification Of The Assumptionsmentioning
confidence: 99%